Study of the probability of resistance to phage infection in a collection of clinical isolates of Pseudomonas aeruginosa in relation to the presence of Pf phages - Lucía Blasco; Clara Ibarguren-Quiles; Carla López-Causape; Lucía Armán; Antonio Barrio-Pujante; Inés Bleriot; Olga Pacios; Laura Fernández-García; Concha Ortiz-Cartagena; Rafael Cantόn; Antonio Oliver; María Tomás (Microbiology Spectrum)
ABSTRACT Pseudomonas aeruginosa is a bacterial pathogen that is a major cause of lung infections in cystic fibrosis (CF) and other patients. Isolates of P. aeruginosa from CF patients commonly carry filamentous phages (Pf phages), which constitute a family of temperate phages known to be related to biofilm production and antibiotic sequestration. In this study, we identified 12 new Pf phage genomes in a collection of clinical isolates of P. aeruginosa from CF patients. Study of the anti-phage defense systems in the bacterial isolates revealed the presence of 89 such systems, of which eight were encoded in the Pf phage genomes. Finally, although a weak relation between resistance to phage infection and the number of anti-phage defense systems was detected, it was observed that the phage resistance was related to the presence of Pf phages and the anti-phage defense systems encoded in these phages.IMPORTANCEBacteria harbor a wide range of defense mechanisms to avoid phage infections that hamper the application of phage therapy because they can lead to the rapid acquisition of phage resistance. In this study, eight anti-phage defense systems were found in the genome of 12 Pf phages that were presents in 56% of the CF isolates of P. aeruginosa. The high prevalence of these phages underlines the importance of our findings about newly discovered filamentous phages and the role of these phages in resistance to phage infections. Thus, the knowledge of the anti-defense system in the Pf phage genomes could be useful in assessing the possible application of phage therapy to treat an infectious disease.